Don't fear the CRISPR. Issue 11 (21st October 2016) - Lowe, Derek
Abstract : Does simple gene-editing mean the end of traditional medicinal chemistry? Probably not. Abstract : Does simple gene-editing mean the end of traditional medicinal chemistry? Probably not.